2010
DOI: 10.1007/s00436-010-1779-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, salinity, and pH on the survival and activity of marine cercariae

Abstract: Alterations of abiotic factors due to global climate change are predicted to impact disease dynamics, particularly for pathogens with complex life cycles involving free-living infectious stages, such as the cercariae of trematode parasites. Previous investigations of cercarial output, longevity, and infectivity suggest an overall increase in trematode transmission in response to elevated temperature. However, while increased temperature will likely be accompanied by changes in salinity and pH in marine ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…In further support of this hypothesis, pH values between 7.7 and 7.9 increased the mortality of larval brittlestar Ophiothrix fragilis in comparison with the control pH value of 8.1 [69]. For parasites, Koprivnikar et al [70] reported an interaction between pH (range = 7.8 to 8.2), salinity and time affecting the survival of the larval stages of the digenean Acanthoparyphium spinulosum. Thus, the potential interaction between pH and the decrease in the number of parasites cannot be disregarded without experimental evidence.…”
Section: Statistical Associations Between Environmental Variables Andmentioning
confidence: 49%
“…In further support of this hypothesis, pH values between 7.7 and 7.9 increased the mortality of larval brittlestar Ophiothrix fragilis in comparison with the control pH value of 8.1 [69]. For parasites, Koprivnikar et al [70] reported an interaction between pH (range = 7.8 to 8.2), salinity and time affecting the survival of the larval stages of the digenean Acanthoparyphium spinulosum. Thus, the potential interaction between pH and the decrease in the number of parasites cannot be disregarded without experimental evidence.…”
Section: Statistical Associations Between Environmental Variables Andmentioning
confidence: 49%
“…In the ordination, this parasite group is distributed at the bottom, indicating that they are more common in autumn and winter. Koprivnikar et al (2010) indicated 18 A. Özer and D.Y. Kırca that some hydrological conditions such as temperature and salinity influence the abundance and distribution of the free-living stages of the parasites.…”
Section: Discussionmentioning
confidence: 98%
“…Koprivnikar et al (2010) indicated that some hydrological conditions such as temperature and salinity influence the abundance and distribution of free-living stages of the parasites, representing in our context the completion of the digenean life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In some trematode species, however, there is no second intermediate host; cercariae encyst on various substrates and become metacercariae, awaiting ingestion by a definitive host (Galaktionov and Dobrovolskij 2003). Multiple studies have documented how sensitive cercariae and metacercariae attached to external substrates are to abiotic conditions, such as temperature (Studer et al 2010;Morley and Lewis 2013), salinity (Lei and Poulin 2011) and pH (Koprivnikar et al 2010;MacLeod and Poulin 2015).…”
Section: Introductionmentioning
confidence: 98%